A Nano-CuO doped sodium aluminosilicate composite ceramic with high efficiency against streptococcus mutans for dental restorative materials. Issue 19 (1st October 2022) - Fu, Rumin; Xiao, Cairong; Zhang, Zhekun; Ren, Kunyu; Zhou, Zhengnan; Wang, Zhengao; Ning, Chengyun; Deng, Chunlin; Zhou, Lei; Yu, Peng; Wang, Xiaolan; Tan, Guoxin
Abstract: Ceramic-based materials are widely used as dental restorative materials due to their excellent corrosion resistance and low shrinkage. However, the pathogenicity caused by abnormal adhesion and colonization of these dental restorative materials by bacteria in the oral cavity significantly affects the restorative results. Therefore, we report an efficient anti-Streptococcus mutans ( S. mutans ) ceramic material achieved by introducing small copper oxide nanoparticles into the sodium aluminosilicate ceramic material. Our results show that the composite ceramic can efficiently kill S. mutans (up to 99.99% antibacterial rate) and has excellent biocompatibility. By examining copper ion release assay, SEM observation, MTT, total protein, and DNA content after co-culture of bacteria, we speculate that copper ions in the composite ceramic disrupt the permeability of S. mutans membrane, affect the respiratory system of bacteria, and disrupt DNA proliferation thereby affecting the regular life activity of bacteria and eventually killing S. mutans . Based on our work, it is feasible to develop an efficient antimicrobial material for restorative dentistry by introducing copper ions into the ceramic materials, providing a new perspective for designing high-performance antimicrobial dental restorative materials.